Integration of advanced practice providers into the Israeli healthcare system - Aaron, Eliana Marcus (Isr J Health Policy Res, 2016)
Many countries around the world have integrated various types of Advanced Practice Providers (APPs) into their healthcare systems. The main motivating factors for recognizing and developing APPs worldwide include physician shortages and the need for improved access or delivery (US, France, Belgium, Scotland, Switzerland), reduced residency hours (US, UK), shortages in underserved regions (US, Canada, Finland, Australia), and cost containment (Germany, Netherlands, UK, US). Israel is experiencing a shortage of physicians in peripheral geographic regions and in critical medical specialties. Recent by-laws approved by the Knesset (Parliament), combined with Israel Ministry of Health (MOH) policies, have thus far been unable to fully address the shortages. To understand the potential contribution of APPs in Israel, we evaluated the international historical foundations and development of APP roles. We assessed how APPs have impacted healthcare in other countries by analyzing public data and published international research about APP education, safety, quality of care, motivators, barriers, and impact. We found that APPs are recognized in dozens of countries, and have similar scopes of practice, graduate level education requirements (in developed countries), and clinical training. At the same time, there is wide variability among countries in the actual function and independence of the advanced practice nurse (APN), particularly the nurse practitioner (NP). APPs have been established as cost effective, safe healthcare providers who improve healthcare access. Israel has begun to introduce APPs, specifically NPs, in a variety of fields, including geriatrics, palliative care and diabetic care. We recommend a rapid expansion of existing and new APP roles into the Israeli healthcare system based on evidence and the recommendations of international evaluations by non-government organizations. By shifting the education to a university setting, mirroring successful, evidence-based, and established APP models found internationally, Israel could lessen the projected Israeli physician shortage, improve healthcare access in specific areas, and bolster existing resources towards a larger and richer pool of healthcare providers in Israel.